PENGARUH LEVERAGE, UKURAN PERUSAHAAN, DAN ARUS KAS OPERASI TERHADAP PEMILIHAN METODE REVALUASI ASET TETAP - Fadel Muhamad Fadillah, - (2019)
This research is using quantitive study aimed to see whether there are influence of leverage, firm size, and cash flow from operating activities in choosing the revaluation method on fixed asset. This study uses manufacturing companies listed in Indonesian Stock Exchange for period 2015-2017 as population. Sample selected by purposive sampling and collected 130 manufacturing companies. Testing the hypothesis in this study was used Regression Logistic Analisys using SPSS version 25 analysis tool with a significant level of 0.05%. The result of these test indicate that (1) leverage has a significant positive influence in choosing the revaluation method on fixed asset (2) firm size has no significant influence in choosing the revaluation method on fixed asset (3) cash flow from operating activities has no significant influence in choosing the revaluation method on fixed asset (4) leverage, firm size, and cash flow from operating activities have been able to explain choosing revaluation method on fixed asset about 5.5%.